Transformation Of Dgt Tax Intelligence in Coretax - Jannah, Uzlifatul; Rifai, Ahmad (Ilomata International Journal of Tax and Accounting, 2024)
Through Tax Reform Volume III, the Directorate General of Taxes (DGT) introduced the Tax Administration Core System (SIAP) or Coretax which aims to revolutionize the tax administration process to increase tax revenue and taxpayer compliance. This study aims to explore changes in the tax intelligence business process, one of the business processes in Coretax. This study is an exploratory study conducted by digging up in-depth information from 14 respondents who are business process owners, users of intelligence reports, and strategic leaders to be then compared with its implementation at the Australian Taxation Office. The study results indicate that the Coretax Application has excellent potential to produce actionable intelligence, namely the results of intelligence activities that are relevant, contextual, and can be used immediately. For this reason, intensive training is needed regarding the application and additional features to increase the effectiveness of the application, data integration to accelerate the exploration of taxpayer potential and ensure the relevance of the information presented, as well as continuous updates to the Coretax Application to face the dynamics of the global economy and technology.